MONTE CARLO ANALYSIS OF THE LATITUDINAL SYMMETRY OF THE GLOBAL BUOYANCY FLUX DISTRIBUTION - Oliver D.H. (My University, 2002)
Both the density of terrestrial hot spots and their associated buoyancy flux show non-random distributions. These distributions are bimodal and symmetric about the equator with maxima occurring between 20 and 30° latitude. The buoyancy flux distributions are not an artifact of data bin width or bin spacing. Monte Carlo analysis performed on two independent buoyancy flux estimates shows that the symmetry as measured by the correlation between paired bands of latitude is statistically significant. Excess buoyancy flux in mid-latitude regions has broad implications regarding material and heat flux within the mantle. The Earth's rotation may be a factor in the migration to and/or the generation of excess low-viscosity, thermally buoyant material in mid-latitude regions.